2009
DOI: 10.1111/j.1540-8167.2009.01490.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Multichannel Holter ECG Recording in the Third Intercostal Space for Detecting Type 1 Brugada ECG: Comparison with Repeated 12‐Lead ECGs

Abstract: Multichannel Holter ECG recording in the third intercostal space is more sensitive and useful for the diagnosis of type 1 Brugada ECG than repeated 12-lead ECGs or multichannel Holter ECG in the standard position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…Additionally, they reported that the instability and heterogeneity of repolarization within the RVOT epicardium was associated with arrhythmogenesis in Brugada syndrome [23]. Shimeno et al [24] reported that Holter-ECG recording at the third intercostal space was more sensitive for detecting spontaneous type-1 ECG patterns than that at the standard positions. Another group reported that the electrophysiological mechanism in patients with Br-S involved delayed depolarization over the anterior aspect of the RVOT epicardium, and that catheter ablation over the abnormal depolarization was effective for eliminating VF and normalizing the Brugada ECG pattern [25].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, they reported that the instability and heterogeneity of repolarization within the RVOT epicardium was associated with arrhythmogenesis in Brugada syndrome [23]. Shimeno et al [24] reported that Holter-ECG recording at the third intercostal space was more sensitive for detecting spontaneous type-1 ECG patterns than that at the standard positions. Another group reported that the electrophysiological mechanism in patients with Br-S involved delayed depolarization over the anterior aspect of the RVOT epicardium, and that catheter ablation over the abnormal depolarization was effective for eliminating VF and normalizing the Brugada ECG pattern [25].…”
Section: Discussionmentioning
confidence: 97%
“…24 Serial 12-leads ECG Holter recordings (at the fourth, third, and second intercostal space) are, therefore, of paramount importance to detect a spontaneous ECG pattern in asymptomatic subjects. 25 Conflicting evidence exists on the prognostic value of PVS in BS. The second consensus report on BS, published in 2005, considered the PVS as the cornerstone of the therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…A higher precordial position might have increased the prevalence of type 1 BrS33; therefore, the prevalence of spontaneous and drug‐induced type 1 BrS may be underestimated.…”
Section: Discussionmentioning
confidence: 99%